Mixed metamorphic and fluid graphite deposition in Palaeoproterozoic supracrustal rocks of the Lewisian Complex, NW Scotland - Parnell, John; Brolly, Connor; Boyce, Adrian J. (Terra Nova, 2021)
Graphite deposits may form alternatively by metamorphism of sedimentary rocks and from fluids. Both types occur in supracrustal successions within the Lewisian Complex of Northwest Scotland, and similarly in Palaeoproterozoic supracrustal rocks across the North Atlantic region in Canada, Greenland and Scandinavia. Carbon isotope compositions show that the graphite in Scotland had a mixed origin from metamorphism of sedimentary organic matter (schists) and the decarbonation of limestones (marbles). Raman spectroscopy shows that most of the graphite in Scotland exhibits some structural disorder, unlike the complete order in graphite vein ore deposits across the region. Exceptionally, where graphite was precipitated from fluid, in albitized rock in Tiree and Scardroy, it is fully ordered. While organic matter may survive granulite facies metamorphism without being transformed to fully ordered graphite, it can yield commercially more valuable ordered graphite when mobilized in a fluid.